Market-friendly agricultural development: Implications for seeds and smallholders in Sub-Saharan Africa. (September 2017) - Sutcliffe, Chloe
Across Sub-Saharan Africa, efforts to produce and supply the agricultural technologies that are expected to intensify smallholder agricultural production are strongly market-oriented. Here, the case of maize seeds in Malawi provides new insights into some of the implications of this orientation. Malawi presents a context where market liberalization coupled with a national input subsidy programme has led to the growth of corporate power within the formal maize seed system and a strong reliance upon commercial providers to breed, multiply and diffuse new cultivars. At both the local and national levels, facets of this market-orientation mean that poverty reduction and climate change adaptation goals may not be met. In order to address these potential shortcomings, multiple measures are required. Institutions are needed to oversee the coordination of appropriate breeding and marketing efforts by corporate actors within the formal seed system; research programmes are required which can enhance understandings of genetic evolution within farmer-saved varieties and its implications for climate resilience; and policies must be carefully implemented which can support market participation by the poorest.